I need to factor these four problems:
2
3x -1/3
2
(y-5) -36
2
(2y-7) -1
16
x -1
PLEASE, please please help me!!!!!
It seems factored to my divine eye.
First 36=6^22
(y-5) -36
Thus,
Difference of two squares
We have,
(y-5-6)(y-5+6)=(y-11)(y+1)
Same idea since 1=1^22
(2y-7) -1
We have,
(2y-7-1)(2y-7+1)=(2y-8)(2y-6)
Factor the twos,
2(y-4)*2(y-3)
Thus,
4(y-4)(y-3)
Difference of two squaures on 1=1^2 we have,16
x -1
(x^8+1)(x^8-1)
Thus,
(x^8+1)(x^4+1)(x^4-1)
Thus,
(x^8+1)(x^4+1)(x^2+1)(x^2-1)
Thus,
(x^8+1)(x^4+1)(x^2+1)(x+1)(x-1)